Pembentukan Jaringan Lunak Saat Pencetakan Implan dengan Laser Diode - Suliana Suliana; Trijani Suwandi (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Currently, the development of lasers in the medical world of dentistry is very rapid. There are many treatments in dentistry that we can use with lasers, one of which is implants. An effective, practical, and safe laser method for treatment in and around implants that requires soft tissues to either expose the implant for the restorative phase or reshape the gingival margin for aesthetics is the Diode Laser. Case report: a woman wants to have an implant placed on tooth 26 so that she can chew well and the other teeth do not shift. The implant installation technique with 2 stages of surgery can only be done one year later due to the covid 19 pandemic. The gingival opening is done using laser diode for healing installation with a diameter of 5 mm and 5 mm in height. Installation of healing is done without suturing because the diode laser method is minimally invasive and gives a good healing result for the soft tissue Conclusion: The diode laser method is very effective and safe for soft tissue formation during implant treatment it is minimally invasive.